Staging Loss
XXII, 265 p. 22 illus., 20 illus. in color.
Keywords: This book locates and critically theorises an emerging field of twenty-first century theatre practice concerned, either thematically, methodologically, or formally, with acts of commemoration and the commemorative. With notions of memorial, celebration, temporality and remembrance at its heart, and as a timely topic for debate, this book asks how theatre and performance intersects with commemorative acts or rituals in contemporary theatre and performance practice. It considers the (re)performance of history, commemoration as a form of, or performance of, ritual, performance as memorial, performance as eulogy and eulogy as performance. It asks where personal acts of remembrance merge with public or political acts of remembrance, where the boundary between the commemorative and the performative might lie, and how it might be blurred, broken or questioned. It explores how we might remake the past in the present, to consider not just how performance commemorates but how commemoration performs.